Beta-blockers after percutaneous coronary intervention for acute myocardial infarction and non-reduced left ventricular ejection fraction - Jeong, Jun-Chang; Park, Jong-Il; Kim, Byung-Jun; Kim, Hong-Ju; Choi, Kang-Un; Nam, Jong-Ho; Lee, Chan-Hee; Son, Jang-Won; Park, Jong-Seon; Her, Sung-Ho; Chang, Ki-Yuk; Ahn, Tae-Hoon; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundData on the clinical impact of beta-blockers (BBs) in patients with myocardial infarction (MI) who had non-reduced left ventricular ejection fraction (LVEF) after percutaneous coronary intervention are limited.MethodsFrom 2016 to 2020, we evaluated a cohort of 12,101 myocardial infarction patients with a non-reduced LVEF (≥40%) from the Korean Acute Myocardial Infarction Registry V. Patients were divided into two groups based on their BB (carvedilol, bisoprolol, or nebivolol) treatment at discharge: with beta-blocker treatment (BB, n = 9,468) and without beta-blocker treatment (non-BB, n = 2,633). The primary endpoint after discharge was the occurrence of patient-oriented composite endpoints (POCEs), including all-cause mortality, any MI, or any revascularization at 1-year follow-up.ResultsThe median follow-up period was 353 days (interquartile range, 198–378 days). At 1-year follow-up, no significant differences were observed in the primary endpoint between the BB group and the non-BB group. Before propensity score (PS) matching, the POCE incidence was 3.1% in the BB group vs. 3.4% in the non-BB group [hazard ratio (HR) 0.86, 95% confidence interval (CI) 0.68–1.09, p = 0.225]. After PS matching, the POCE incidence remained similar between the two groups (3.7% vs. 3.4%, HR 1.01, 95% CI 0.76–1.35, p = 0.931). Individual outcomes, including all-cause mortality, myocardial infarction, and revascularization, also showed no significant differences between the two groups. Independent predictors of 1-year POCEs after discharge were age, chronic kidney disease, reduced LVEF, and multivessel disease.ConclusionBB treatment in patients with acute MI and non-reduced LVEF was not associated with a significant reduction in cardiovascular outcomes at 1-year follow-up.